2014
DOI: 10.4149/gpb_2013084
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of nitric oxide in hepatic injury secondary to renal ischemia-reperfusion (I/R) injury

Abstract: Hepatic injury secondary to renal I/R injury has been documented in several studies. This study aimed to investigate the role of NO in hepatic injury secondary to renal I/R in rat model. Sprague-Dawley rats (n = 48) were divided into 4 equal groups; sham-operated, I/R injury group (45 min of bilateral renal ischemia), L-arginine group (I/R with 300 mg/kg L-arginine, 20 min before ischemia), L-NAME group (I/R with 50 mg/kg L-NAME, 20 min before ischemia). L-NAME (NO synthase inhibitor) caused significant elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Cerebral ischemia-reperfusion (I/R) injury is mainly caused by the restoration of blood perfusion following brain tissue ischemia [ 1 ]. The pathophysiological mechanism of cerebral I/R injury is extremely complex and includes the oxidative stress response, intracellular calcium overload, toxic effects of excitatory amino acids, apoptosis, mitochondrial dysfunction, inflammatory reaction, and so on [ 2 , 3 ]. Cerebral I/R injury can cause apoptosis of hippocampal nerve cells and affect nerve function [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral ischemia-reperfusion (I/R) injury is mainly caused by the restoration of blood perfusion following brain tissue ischemia [ 1 ]. The pathophysiological mechanism of cerebral I/R injury is extremely complex and includes the oxidative stress response, intracellular calcium overload, toxic effects of excitatory amino acids, apoptosis, mitochondrial dysfunction, inflammatory reaction, and so on [ 2 , 3 ]. Cerebral I/R injury can cause apoptosis of hippocampal nerve cells and affect nerve function [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…NO has many important roles in the liver, including apoptosis inhibition [4,5], liver regeneration [6], and injury prevention [7]. Sumii et al have also shown that NO can increase hepatic function [3].…”
Section: Introductionmentioning
confidence: 99%